Relaxing or arousing environments (through color and music) for fostering designer's creativity. Issue 4 (2nd October 2022) - Chulvi, Vicente; Royo, Marta; Agost, María-Jesús; García-García, Carlos; Ruiz-Pastor, Laura
ABSTRACT: Within the literature devoted to studying the influence of environment factors on people's creativity, the majority analyzed these factors as isolated elements and assess individual's creativity in general. The aim of this work is to analyze the influence of some of these environmental factors on the design outcomes in terms of creativity, considering the potential emotion it can cause (relaxation or arousal). An experiment was developed to test the results generated in different settings combining environment factors that enhance creativity, in which designers were asked to develop different creative concepts. Different colors and music were combined in order to set arousing and relaxing environments. Results point to differences in the creativity parameters, according to the environment in which designers worked.